Zinc: Multidimensional Effects on Living Organisms - Math P. Cuajungco; Maria Soledad Ramirez; Marcelo E. Tolmasky (Biomedicines, 2021)
Zinc is a redox-inert trace element that is second only to iron in abundance in biological systems. In cells, zinc is typically buffered and bound to metalloproteins, but it may also exist in a labile or chelatable (free ion) form. Zinc plays a critical role in prokaryotes and eukaryotes, ranging from structural to catalytic to replication to demise. This review discusses the influential properties of zinc on various mechanisms of bacterial proliferation and synergistic action as an antimicrobial element. We also touch upon the significance of zinc among eukaryotic cells and how it may modulate their survival and death through its inhibitory or modulatory effect on certain receptors, enzymes, and signaling proteins. A brief discussion on zinc chelators is also presented, and chelating agents may be used with or against zinc to affect therapeutics against human diseases. Overall, the multidimensional effects of zinc in cells attest to the growing number of scientific research that reveal the consequential prominence of this remarkable transition metal in human health and disease.